A Genetically Encoded Allysine for the Synthesis of Proteins with Site‐Specific Lysine Dimethylation. (2nd December 2016) - Wang, Zhipeng A.; Zeng, Yu; Kurra, Yadagiri; Wang, Xin; Tharp, Jeffery M.; Vatansever, Erol C.; Hsu, Willie W.; Dai, Susie; Fang, Xinqiang; Liu, Wenshe R.
Abstract: Using the amber suppression approach, N ϵ ‐(4‐azidobenzoxycarbonyl)‐δ, ϵ‐dehydrolysine, an allysine precursor is genetically encoded in E. coli. Its genetic incorporation followed by two sequential biocompatible reactions allows convenient synthesis of proteins with site‐specific lysine dimethylation. Using this approach, dimethyl‐histone H3 and p53 proteins have been synthesized and used to probe functions of epigenetic enzymes including histone demethylase LSD1 and histone acetyltransferase Tip60. We confirmed that LSD1 is catalytically active toward H3K4me2 and H3K9me2 but inert toward H3K36me2, and methylation at p53 K372 directly activates Tip60 for its catalyzed acetylation at p53 K120. Abstract : Zielführende Proteinsynthese : Eine Allysinvorstufe, N ϵ ‐(4‐Azidobenzoxycarbonyl)‐δ, ϵ‐dehydrolysin, wurde in E. coli genetisch eincodiert. Ihre Proteinkonjugation, anschließende Staudinger‐Reduktion und reduktive Aminierung ermöglichten die Synthese von Proteinen mit ortsspezifischer Lysin‐Dimethylierung.